DETECTION AND CONTROL SYSTEM OF DATA AND DELAY MODIFICATION ATTACK ON MINI DISTILLATION COLUMN BASED CYBER PHYSICAL SYSTEM - Panji Mardyaningsih, Wedar
The development of the industrial revolution 4.0 in addition to having a major impact in the form of increased production in the industrial sector also opened a cyber gap for outsiders to pose a threat to the system. The industrial control system was originally only designed to meet the priorities of the SRA (Safety, Reliability, and Availability) at this time began to be pressed to consider the security aspects related to the magnitude of the impact that can be caused by attacks from outsiders such as in the case of Trojans in the Soviet Union and Stuxnet. In creating a secure automation-based CPS system risk management methods consist of risk assessment, attack detection, and mitigation. Risk assessment results in the form of threats with the greatest risk for CPS-based mini distillation columns namely modification threats. Modification of sensor data values and modification of delay are used as scenarios in this thesis. Detection and recovery using roll-forward method via neural network is applied to the scenario modification of sensor data values. As for the detection and recovery time delay, the estimated delay method using PID controller is used.